Commitment Organization, Job Satisfaction dan Work Engagement pada Karyawan Milenial.docx - Dewi, Reza Auliya Yunita (Jurnal Ilmiah Wahana Pendidikan, 2023)
Millennials are often associated with the term 'job hopping' in the field of work. This term refers to how quickly millennial change job and the company in a short time. This action illustrates the lack of commitment of millennial employees to the organization where they work, to increase commitment it is also necessary to increase the job satisfaction and work engagement of millennial employees in an organization. If an employee feels satisfied and happy with his job, he will also indirectly tie himself to the job he is currently occupied, so that this behavior can increase the desire to stay longer in the organization where he works. This research was conducted to test empirically regarding job satisfaction and work engagement on organizational commitment in millennial employees by using multiple regression tests. The number of samples in this study were 109 employees using a purposive sampling technique. The results of the study show that there is a contribution of job satisfaction and work engagement to organizational commitment in millennial employees.